Strategi Pengembangan Ekowisata di Pantai Pangandaran Kabupaten Ciamis Pasca Tsunami - Nugroho, Prasetyo; Yusuf, Muh.; Suryono, Suryono (977-2407769)
jung village and Pangandaran village who has a wealth of natural, culture and diverse appeal so has prospects for the development of ecotourism. From the SWOT analysis can be drawn that many factors influence the development of ecotourism in the Pangandaran Beach. The results showed that the internal factor such as strength (S) has a score of 1.811 and 1.313 scores for weaknesses (W). While External factors consist of Opportunity (O) and Threats (T) has a score of respectively 2.305 and 0.908. It means that is necessary to develop a more intensive and broader. So priority the future development strategy that needs to be done is Utilizing the support of the Government and stakeholders to optimize the function of the airport, Utilizing tourist attractions an attractive and safe then optimize asset development cooperation with travel agents both within and outside the country.